Tingkat Kepuasan Pasien RSIA Siti Hawa dalam Upaya Peningkatan Kualitas Pelayanan Menggunakan Metode Service Quality (SERVQUAL) - Apriani, Rika; Nurcahyo, Gunadi Widi (Jurnal Sistim Informasi dan Teknologi, 2021)
Patient satisfaction is an important indicator in improving the quality of the hospital. RSIA Siti Hawa always tries to improve the quality of the hospital in order to provide excellent service to patients. One of the efforts made to improve the quality of the hospital is by knowing the level of patient satisfaction. The purpose of this study was to determine the extent of patient satisfaction with the Siti Hawa Hospital service so that it can assist management in evaluating and improving services to improve quality. This research was conducted using the Service Quality (SERVQUAL) method which has five dimensions, namely tangible (physical evidence), reliability (reliability), responsiveness (responsiveness), assurance (assurance) and empathy (empathy). This measurement is carried out to identify the patient's expectations and perceptions so that from the five dimensions of Service Quality, the overall service quality can be seen by looking at the value of the gap that occurs due to the mismatch between patient expectations and perceptions. The data processed in this study were questionnaire data from 30 respondents / patient. The result of this test is that the service quality of the five dimensions of service quality consisting of 14 question attributes has a positive gap value. The highest gap value is 0.47 in the 12th question attribute regarding politeness and friendliness of officers in providing services, and the lowest gap value is in the 6th attribute with a value of 0.27 regarding the timeliness of service schedules. Based on the dimensions, the order of the rank dimensions from the highest is empathy, assurance, responsiveness, tangible and reliability. Based on the results of this study, it can be concluded that the services provided by RSIA Siti Hawa to patients can be said to be good, and the results of these measurements can be used as an evaluation in improving the quality of hospital services.